Dentists' knowledge, attitudes, and professional behavior regarding silver diamine fluoride: A cross-sectional questionnaire study - Jiksha Mehlawat; Charu Mohan Marya; Ruchi Nagpal; Sakshi Kataria; Pratibha Taneja (Wolters Kluwer Medknow Publications, 2022)
Background: Dental caries is a major public health problem and is handled through either treatment or prevention. Unlike other fluoride-based caries preventive agents, silver diamine fluoride (SDF) can simultaneously prevent and arrest coronal and root dentine caries. Aim: The aim of this study is to assess dentists' educational experiences, knowledge, attitudes, and professional behavior regarding SDF use for caries prevention. Methodology: For the cross-sectional survey, a prevalidated questionnaire comprising of 33 questions was being prepared through the Google survey tool of Gmail and was sent to 200 dentists in North India region through Whatsapp groups of different communities or specialties. Data analysis was done using IBM SPSS version 16. Results: The response rate of 63.5% was received from 200 dentists, among which 28.8% were general practitioners and 35.2% were both academic and clinical practitioners. Only 5.6% respondents came up having been very well educated about SDF during Bachelors in Dental Surgery and Master of Dental Surgery in the classroom setting and 3.2% in the clinical setting. There were 14.4% participants who reported that they knew very well about what SDF is used for in dentistry, and 9.6% knew how SDF is used for treatment of tooth hypersensitivity, 24.8% knew how SDF is used to treat dental caries. The attitudes of the dentists toward SDF were positive. SDF use was considered a good treatment alternative for restorations in children with behavioral problems (17.6%), for patients who were medically fragile (12%) or had severe dental anxiety (19%) and strongly agreed to it. Conclusion: Results suggested that the majority of respondents were lacking in knowledge regarding usage of SDF in dentistry.